Удосконалення технології паст кисломолочних з прянощами - Бандура (Кузьмик), Ульяна Геннадіївна (My University, 2018)
Дисертаційна робота присвячена удосконаленню технології паст кисломолочних і застосуванню у їх складі науково обґрунтованих композицій натуральних прянощів, які виявляють функціонально-технологічні властивості. Обґрунтовано вибір прянощів для використання у складі паст кисломолочних та визначено здатність до поєднання з кисломолочною основою за органолептичними та фізико-хімічними показниками; визначено рекомендований вміст прянощів, спосіб та технологічні параметри введення. Розроблено науково-обґрунтовану систему комбінування натуральних прянощів для паст кисломолочних. Досліджено антиоксиданту та антимікробну дію розроблених композицій прянощів на типові контамінанти кисломолочних продуктів, що обумовлено природнім вмістом у прянощах фенольних сполук і терпенів. Доведено технологічну ефективність використання функціонально- технологічних властивостей крупи гречаної несмаженої як вологозвязуючого компоненту у складі паст кисломолочних. Розроблено математичну модель комплексної оцінки якості паст кисломолочних. Обґрунтовано можливість подовження терміну зберігання паст кисломолочних з прянощами на основі сиру кисломолочного – до 7 діб, на основі сметани – до 10 діб за температури (4 ± 2) °С. The dissertation is concerned with the improvement of technology of fermented dairy paste by developing and applying scientifically substantiated compositions of spices. The prospect of using the technology of fermented dairy natural spices is substantiated for their enrichment by the complex of biologically active substances, stabilization of quality indices of finished products during their storage. According to the criteria of selection, the compatibility of spices with the fermented dairy base was determined, as well as the rational content of individual spices in the composition of fermented dairy pastes based on lactic cheese and sour cream (from 0.1 % to 1.0 %) was established. Dominant spices were selected to be the base for the formation of spice compositions. The method and technological parameters of the introduction of spices are determined – in the dry molten form with the particle size not more than 0.4 mm; sumach – in the form of an extract based on the milk whey. The optimum technological parameters for obtaining sumach extract using a rotor-pulse apparatus are the following: hydromodule – 1:10, extractant – milk whey; extraction temperature – (80 ± 2) °C; the process duration is 5-10 minutes; a particle size – up to 2 mm. The physicochemical, microbiological indices asl well as functional and technological properties of selected spices were investigated. It is proved that the spices are characterized by high content of carbohydrates (2.90...12.94 %) and high antioxidant activity. This is due to the presence of essential oils in the natural spices, as well as the content of phenolic compounds such as tannin and rutin. The score scale was developed and the criteria for evaluating the taste and aroma properties of fermented dairy pastes with spices were determined. The composition formulation was determined by analyzing the compatibility of the taste and aroma characteristics of various types of spices. Profilographies of the taste and aroma properties of fermented dairy pastes with spices were constructed in order to determine the rational proportions of composition formulation. The expediency of using spice compositions in the technology of fermented dairy pastes is substantiated. For the first time it was determined that spice compositions are characterized by high content of biologically active substances: the content of phenolic compounds – 42.4...223.4 mg/100 g; rutin – 2.2...3.1 mg/100 g; catechin – 1.6...5.6 mg/100 g; tannin – 0.4...9.4 mg/100 g.
Keywords: кафедра технології молока і молочних продуктів; аромат; біологічно активні речовини; композиції прянощів; крупа гречана несмажена; паста кисломолочна; прянощі; стабілізація структури; aroma; biologically active substances; spice compositions; buckwheat groats; non-fried; sour-milk paste; spices; stabilization of the structure